2003
DOI: 10.1001/jama.289.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Treatment of Migraine With an Angiotensin II ReceptorBlocker

Abstract: ContextThere is a paucity of effective, well-tolerated drugs available for migraine prophylaxis.Objective To determine whether treatment with the angiotensin II receptor blocker candesartan is effective as a migraine-prophylactic drug.Design and Setting Randomized, double-blind, placebo-controlled crossover study performed in a Norwegian neurological outpatient clinic from January 2001 to February 2002.Patients Sixty patients aged 18 to 65 years with 2 to 6 migraine attacks per month were recruited mainly from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
181
2
32

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(221 citation statements)
references
References 25 publications
6
181
2
32
Order By: Relevance
“…89 Candesartan decreased migraine-related disability, but had no effect on use of drugs for acute migraine attacks. 90 In contrast, the ARB telmisartan was not better than placebo in reducing monthly migraine attacks by ≥50 %. 91 Comparative Effectiveness of Drugs for Prevention of Episodic Migraine.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…89 Candesartan decreased migraine-related disability, but had no effect on use of drugs for acute migraine attacks. 90 In contrast, the ARB telmisartan was not better than placebo in reducing monthly migraine attacks by ≥50 %. 91 Comparative Effectiveness of Drugs for Prevention of Episodic Migraine.…”
Section: Resultsmentioning
confidence: 96%
“…84 Individual RCTs demonstrated that three off-label beta blockers-acebutolol 85 Table 8), improved headache index scores by ≥50 %, and reduced depression symptoms in adults with comorbid hypertension and depressive symptoms for whom previous preventive antimigraine drugs had been ineffective. 88 The ACE inhibitor lisinopril 89 (233 attributable events per 1,000 treated, 95 % CI, 124 to 343) and the ARB candesartan 90 (350 attributable events per 1,000 treated, 95 % CI, 219 to 481) were better than placebo in reducing monthly migraine attacks by ≥50 %. Lisinopril was better than placebo in reducing pain measured with the Short Form 36 (SF-36) questionnaire, but did not decrease use of drugs for acute migraine attacks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the angiotensin AT 1 receptor antagonist candesartan (Tronvik et al 2003) also seems to be effective as prophylactic antimigraine drug, which may be generalized to other drugs from the same class as suggested by an open-label study in 24 patients using olmesartan (Charles et al 2006). In addition, genetic studies suggest an association between ACE gene polymorphisms and migraine (Paterna et al 2000).…”
Section: Angiotensin Receptorsmentioning
confidence: 96%
“…All of the non-patient-reported measures are classified as either diagnosis-related 42,44,45 (Table 2) or treatment-and preventionrelated 42,[44][45][46][47][48] (Tables 3 and 4). The RAND authors assert that screening for headaches is not recommended because the problem is symptomatic.…”
Section: Gagne Et Al 142 Table 2 Diagnosis-related Migraine Qualitymentioning
confidence: 99%